Peran Kepemimpinan Autentik dan Person-Job Fit terhadap Turnover Intention pada Karyawan Generasi Z - Andrey Afandi; Bagus Wicaksono; Pratista Arya Satwika (Universitas Negeri Surabaya, 2022)
Human resources are an important element in the company to achieve the company's vision and mission. Companies must be able to pay attention to the needs of employees properly, otherwise employees will choose to leave the company or have turnover intentions. Generation z, which is the newest generation in the company today, has a tendency to want to leave work within three months. Preliminary studies show the results that the ratio of the turnover percentage of generation z employees is higher than employees other than generation z. This study aims to determine the relationship between authentic leadership and person-job fit with turnover intention in Generation Z employees. Employees who work under the direction of authentic leaders enjoy their work more and feel more satisfied with the atmosphere in their organization. In addition, the suitability of the employee's ability to the demands of the job also has an effect on employee turnover intention. The sample of this research is 93 employees of generation z structural sewing in a textile company. The study was analyzed using multiple regression analysis techniques. The research instruments used in this study were the turnover intention scale, the authentic leadership scale, and the person-job fit scale. The results showed that there was a significant relationship between authentic leadership and person-job fit with turnover intention (p<0.05), and partially showed that there was no relationship between authentic leadership and turnover intention (p>0.05). Then the next results showed a significant relationship between person-job fit and turnover intention (p <0.05). Perusahaan harus bisa memperhatikan kebutuhan karyawandengan baik, jika tidak karyawan akan memilih untukmeninggalkan perusahaan atau turnover intention. Generasi zyang menjadi angkatan terbaru di perusahaan saat ini,memiliki kecenderungan ingin meninggalkan pekerjaandalam waktu tiga bulan. Studi pendahuluan menunjukkanhasil bahwa perbandingan persentase turnover karyawangenerasi z lebih tinggi daripada karyawan selain generasi z.Penelitian ini bertujuan untuk menganalisis hubungan antarakepemimpinan autentik dan person-job fit dengan turnoverintention pada karyawan generasi z. Sampel penelitian iniadalah 93 karyawan generasi z bagian struktural sewing disebuah perusahaan tekstil. Penelitian dianalisis menggunakanteknik analisis regresi berganda. Instrumen penelitian yangdigunakan dalam penelitian ini adalah skala turnoverintention, skala kepemimpinan autentik, dan skala person-jobfit. Hasil penelitian menunjukan ada hubungan signifikanantara kepemimpinan autentik dan person-job fit denganturnover intention (p<0,05), dan secara parsial menunjukanbahwa tidak ada hubungan antara kepemimpinan autentikdengan turnover intention (p>0,05). Kemudian hasilselanjutnya menunjukan hasil yang hubungan signifikanantara person-job fit dengan turnover intention (p<0,05).Kecocokan antara kemampuan karyawan dengan tuntutanpekerjaan membuat karyawan memiliki keterlibatan kerjayang tinggi. Selain itu, pemimpin dengan gaya autentik dapatmelibatkan karyawan generasi z dalam pekerjaan danmendengarkan ide-ide karyawan sebelum mengambilkeputusan. Namun, banyak karyawan generasi z memilihbekerja dalam tim karena mereka dapat mengembangkan diridan mendapatkan pengakuan, sehingga pemimpin autentiktidak memiliki peran yang tinggi terhadap turnover intentionkaryawan generasi z secara parsial.